Characterizing the Leaf Transcriptome of Chrysanthemum rhombifolium (Ling et C. Shih), a Drought Resistant, Endemic Plant From China - Zhang, Wenjie; Xu, Hongyuan; Duan, Xiaxia; Hu, Jing; Li, Jingjing; Zhao, Liang; Ma, Yueping (Frontiers in Genetics, 2021)
Chrysanthemum rhombifolium (Ling et C. Shih), an endemic plant that is extremely well-adapted to harsh environments. However, little is known about its molecular biology of the plant's resistant traits against stress, or even its molecular biology of overall plant. To investigate the molecular biology of C. rhombifolium and mechanism of stress adaptation, we performed transcriptome sequencing of its leaves using an Illumina platform. A total of 130,891 unigenes were obtained, and 97,496 ( 74.5%) unigenes were annotated in the public protein database. The similarity search indicated that 40,878 and 74,084 unigenes showed significant similarities to known proteins from NCBI non-redundant and Swissprot protein databases, respectively. Of these, 56,213 and 42,005 unigenes were assigned to the Gene Ontology (GO) database and Cluster of Orthologous Groups (COG), respectively, and 38,918 unigenes were mapped into five main categories, including 18 KEGG pathways. Metabolism was the largest category (23,128, 59.4%) among the main KEGG categories, suggesting active metabolic processes in C. rhombifolium. About 2,459 unigenes were annotated to have a role in defense mechanism or stress tolerance. Transcriptome analysis of C. rhombifolium revealed the presence of 12,925 microsatellites in 10,524 unigenes and mono, trip, and dinucleotides having higher polymorphism rates. The phylogenetic analysis based on GME gene among related species confirmed the reliability of the transcriptomic data. This work is the first genetic study of C. rhombifolium as a new plant resource of stress-tolerant genes. This large number of transcriptome sequences enabled us to comprehensively understand the basic genetics of C. rhombifolium and discover novel genes that will be helpful in the molecular improvement of chrysanthemums.